Promoting sustainable development through realizing the demographic dividend opportunity in the digital economy: A case study of Nepal - Tapan Sarker; Shristi Tandukar; Sima Rani Dey (Asian Development Bank Institute (ADBI), 2021)
This paper reports the links between demographic dividend, digital economy, and sustainable development in the context of Nepal. Nepal is one of the countries that has been undergoing a remarkable demographic transition in South Asia in the last few decades, which provides it with the "window of opportunity" for sustainable development. In this regard, an appropriate study in this sector is indispensable to capture the optimum advantage of demographic dividend with the emerging techno-economic paradigm administering the dimensions of sustainability. By using multiple regressions, we analyze the economic variables of demographic dividend as the dependent variable, with the indicators of the digital economy being telecommunication and internet access as independent variables, and for the environment-related issues, greenhouse gas emissions and urbanization as explanatory variables, to understand the convoluted relationship of the influence of demographic dividend on the digital economy. The study provides a decisive rationale for the prospective policy implications necessary to grasp the advantage of demographic dividend by examining the potentials of the digital economy, exploring the environmental dimension that is currently regarded as one of the global issues in the economy. Policy implications and the impact of COVID-19 have also been discussed. The outcome of the research provides a road map for attaining the Sustainable Development Goals for Nepal. The findings and lessons learned will also assist policymakers and future researchers with similar scopes that can strengthen the economy of countries, but not limited to the least developed countries.
Keywords: J11; O32; Q56; 330; demographic dividend; digitalization; environment sustainability; economy; Nepal